2011
DOI: 10.1111/j.1471-0528.2011.03137.x
|View full text |Cite
|
Sign up to set email alerts
|

Infant mortality and subsequent risk of stillbirth: a retrospective cohort study

Abstract: Objective To examine the association between infant mortality in a first pregnancy and risk for stillbirth in a second pregnancy.Design Population-based, retrospective cohort study.Setting Maternally linked cohort data files for the state of Missouri.Population Women who had two singleton pregnancies in Missouri during the period 1989-2005 (n = 320 350).Methods Women whose first pregnancy resulted in infant death were compared with those whose infant from the first pregnancy survived the first year of life. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
4
10
0
Order By: Relevance
“…Although absolute risks were much higher than in western countries, the strength of association of a 3.2-fold recurrence risk observed in our data was consistent with associations observed in western countries [14-16]. Some studies have found slightly higher relative risks [9,17,18], and one study in Afro-American women estimated a four-fold recurrence risk [14].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although absolute risks were much higher than in western countries, the strength of association of a 3.2-fold recurrence risk observed in our data was consistent with associations observed in western countries [14-16]. Some studies have found slightly higher relative risks [9,17,18], and one study in Afro-American women estimated a four-fold recurrence risk [14].…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have found slightly higher relative risks [9,17,18], and one study in Afro-American women estimated a four-fold recurrence risk [14]. A 2-fold recurrence risk has been reported from Israel [11].…”
Section: Discussionmentioning
confidence: 99%
“…This sharp increase became substantial when live births occurred more frequently. Furthermore, the increase is similar to previous studies that used the Kaplan–Meier method to right‐censor live births . Using the Kaplan–Meier approach, we showed that the risk of stillbirth in multiple pregnancies increased considerably after 35 weeks of gestation, with a five‐fold greater overall risk compared with the cumulative incidence method.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the increase is similar to previous studies that used the Kaplan-Meier method to right-censor live births. 1,2,13 Using the Kaplan-Meier approach, we showed that the risk of stillbirth in multiple pregnancies increased considerably after 35 weeks of gestation, with a five-fold greater overall risk compared with the cumulative incidence method. Similarly, the cumulative risk for singleton pregnancies increased sharply after 40 weeks, yielding a 2.5-fold greater overall risk.…”
Section: Discussionmentioning
confidence: 99%
“…Over the same period, there have been changes in stillbirth risk factors. Births to women of higher‐risk groups increased including older mothers, lower socioeconomic status, obese, diabetic, women with previous stillbirths or preterm births, and infants conceived using ART, commonly reported risk factors for stillbirth 10,11,26–28 . Conversely, there were contemporaneous decreases in other high‐risk groups including teenage mothers, smokers, infection, pregnancy hypertension and some chronic conditions, which are also known risk factors for stillbirth 11,28,29,30 …”
Section: Discussionmentioning
confidence: 99%